(untitled) (Research, Society and Development, 2020)
Soybeans are the main raw material for the production of oil used in human food, and the conversion to biodiesel. For biodiesel production, an important prior operation is the deacidification of the oil through the removal of free fatty acids. One of the most advantageous methods for the promotion of deacidification is the liquid-liquid extraction carried out at ambient temperature and atmospheric pressure. The objective of this study was to promote the optimization of the deacidification process. Analysis of peroxide and saponification, density, viscosity, refractive index and water content in the raw material collected in the biodiesel industries of the state was performed. The deacidification was carried out in a 2³ factorial design to evaluate the effect of water content, oil / solvent ratio, and temperature on the percentage of free fatty acid removal and partition coefficient. It was observed that the soybean oil analyzed meets the quality standards established by the legislation, and water content was the most influential variable in the deacidification process, reducing the extraction capacity of the solvent. This study was an experimental and laboratory research of a quantitative nature, where the test conditions were controlled using a factorial design of 23. Concluding with the results that the percentage of water was an inversely influential variable, where in smaller percentages it was possible to extract greater amounts of free fatty acids, aiming at a more efficient extraction.